Notes on two green plankton found in Bangladesh - Islam, AKM Nurul; Alfasane, Md Almujaddade (Bangladesh Journal of Plant Taxonomy, 2005)
Not available. Key words: Green planktonic algae, Chlorococcales, Bangladesh DOI: 10.3329/bjpt.v12i2.606 Bangladesh J. Plant Taxon. 12(2): 97-99, 2005 (December)